Chromatin organization and cytological features of carnivorous Genlisea species with large genome size differences - Tran, Trung D; Cao, Hieu X; Jovtchev, Gabriele; Novák, Petr; Vu, Giang T H; Macas, Jiří; Schubert, Ingo; Fuchs, Joerg (Frontiers in plant science, 2015)
The monophyletic carnivorous genus Genlisea (Lentibulariaceae) is characterized by a bi-directional genome size evolution resulting in a 25-fold difference in nuclear DNA content. This is one of the largest ranges found within a genus so far and makes Genlisea an interesting subject to study mechanisms of genome and karyotype evolution. Genlisea nigrocaulis, with 86 Mbp one of the smallest plant genomes, and the 18-fold larger genome of G. hispidula (1,550 Mbp) possess identical chromosome numbers (2n = 40) but differ considerably in chromatin organization, nuclear and cell size. Interphase nuclei of G. nigrocaulis and of related species with small genomes, G. aurea (133 Mbp, 2n ≈ 104) and G. pygmaea (179 Mbp, 2n = 80), are hallmarked by intensely DAPI-stained chromocenters, carrying typical heterochromatin-associated methylation marks (5-methylcytosine, H3K9me2), while in G. hispidula and surprisingly also in the small genome of G. margaretae (184 Mbp, 2n = 38) the heterochromatin marks are more evenly distributed. Probes of tandem repetitive sequences together with rDNA allow the unequivocal discrimination of 13 out of 20 chromosome pairs of G. hispidula. One of the repetitive sequences labeled half of the chromosome set almost homogenously supporting an allopolyploid status of G. hispidula and its close relative G. subglabra (1,622 Mbp, 2n = 40). In G. nigrocaulis 11 chromosome pairs could be individualized using a combination of rDNA and unique genomic probes. The presented data provide a basis for future studies of karyotype evolution within the genus Genlisea.
Keywords: rDNA; single copy probes; chromosome number; repetitive DNA sequences; Genlisea; karyotyping; FISH; epigenetic marks